Assessment of degree of illness acceptance in adolescents with acne - Rolka, Hanna; Krajewska-Kułak, Elżbieta; Dyduch, Małgorzata; Kowalczuk, Krystyna (Nursing Problems / Problemy Pielęgniarstwa, 2010)
Introduction. Acne is an important problem of esthetic nature. Chronic disorder changes on skin often cause the development of subdepression in young people in whom appearance is essential. Aim of the study. Assessment of degree illness acceptance among adolescents aged 15=17 treated due to acne. Material and methods. In the study, we used diagnostic survey. Authors questionnaire included Acceptance of Illness Scale (AIS). The study group included 78 adolescents aged 15-17 lived in Gliwice-Sosnowiec region. Results. In the study group mean value of illness acceptance assessed by AIS scale was 24.7 scores, in adolescents with poor social conditions was 19.7. These adolescents reported that poor social conditions do not allow to go to cosmetic saloon, and private doctors. Almost 79% females and 43% men avoided contacts with peers. Bad feelings: sorrow and grief due to skin changes and not attractive appearance had 75% of responders. Almost 41% of adolescents experienced embarrassment, shame and discomfort due to agonistic behavior of peers. Significant differences in illness acceptance were found between the following groups: duration of disease > 5 years and group suffered from 2 years, group with financial problems and group with no financial problems, unsystematically treated adolescents and cooperative adolescents. Conclusions. Most of adolescents lived in poor social conditions which caused they did not allow to use cosmetics and private doctor visits. Most of responders had bad feelings: sorrow and shame. In opinion of most responders, peers commented their appearance, gibbed, what increased shame and malaise. Responders had mild level of illness acceptance. Illness acceptance was related to duration of skin changes, financial status of family and regularity of treatment. Nursing Topics 2010; 18 (1): 47-52